Alalakh: an account of the excavations at Tell Atchana in the Hatay, 1937-1949 - Woolley, Leonard (Reports of the Research Committee of the Society of Antiquaries of London, 2004)
This monograph describes large-scale excavations undertaken by Sir Leonard Woolley from 1937 to 1939, and again from 1946 to 1949, at the site of Alalakh (modern Tell Atchana) - a late Bronze Age city in the Amuq River valley of Turkey's Hatay Province. Described is the evidence of a series of superimposed palaces and temples, town defences, private houses and graves, in 17 archaeological levels reaching from late Early Bronze Age (Level XVII, c. 2200-2000 BC to Late Bronze Age (Level 0, 13th century BC). Supplementary reports describe the architecture and frescoes, sculptures, and portable objects in fired clay, gold, silver, ivory, stone, and glass.